Transparency and Accountability in the Civil Service (ASN) Promotion Process at the Regional Personnel Agency of Sidoarjo Regency - Ficha Indriana; Fedianty Augustinah; Eny Haryati (International Journal of Social Science and Humanity, 2025)
This research looks into the transparency and accountability in the promotion process for civil servants at the Regional Civil Service Agency (BKD) of Sidoarjo Regency as a component of the continual bureaucratic reform aimed at achieving clean and professional governance. Overall, the promotion process has embraced the digital-based Sidoarjo Smart ASN system and adheres to the merit principle, although obstacles persist in achieving completely transparent and accountable practices. The study centers on four key areas: transparency of public information, responsibility in decision-making, the validity of the merit system, and the efficiency of internal oversight and citizen engagement. A qualitative descriptive method utilizing a case study approach was employed, incorporating in-depth interviews, direct observations, and the analysis of official documents. The results indicate that transparency continues to be administrative in character, accountability is focused vertically instead of being horizontally accountable to the public, and the merit system encounters challenges linked to bureaucratic culture and the integration of competency data. Additionally, internal oversight does not have enough community engagement in assessing promotion procedures. The research suggests improving transparency via interactive publishing, establishing accountability systems based on performance, boosting independent evaluation capabilities, and incorporating digital oversight tools with public engagement. These results are anticipated to provide a basis for creating a civil service management model at the regional government level that is more transparent, accountable, and grounded in integrity.